2004
DOI: 10.2166/nh.2004.0010
|View full text |Cite
|
Sign up to set email alerts
|

Simple water balance modelling with few data - calibration and evaluation: investigations from a Danish Sitka spruce stand with a high interception loss

Abstract: Simple evapotranspiration models with few data requirements and Penman reference evapotranspiration for grass (Eref) limiting the actual evapotranspiration are often used to estimate chemical fluxes in ecosystems. The aim of this paper is to show how much the interception loss might exceed Eref in a wind-exposed Danish Sitka spruce stand and to demonstrate the importance of the evaluation of model performance, here represented by throughfall measurements and chemical fluxes. Precipitation, throughfall, soil mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Spruce had less throughfall than broadleaved species and it is suggested that the percolation in forest ecosystems is largely controlled by canopy throughfall and interception and to a lesser degree by transpiration and soil evaporation. These findings are in accordance with previous studies (Alavi et al, 2001;Ladekarl, 2001;Mossin & Ladekarl, 2004;Christiansen et al, 2006;van der Salm et al, 2006) which found that canopy interception accounted for the major differences in percolation between deciduous and coniferous forests. As future afforestation projects mainly focus on broadleaved forest types it is also relevant to evaluate which deciduous species will yield the highest amount of percolation water and at the same time retain N.…”
Section: Water Balancesupporting
confidence: 93%
See 1 more Smart Citation
“…Spruce had less throughfall than broadleaved species and it is suggested that the percolation in forest ecosystems is largely controlled by canopy throughfall and interception and to a lesser degree by transpiration and soil evaporation. These findings are in accordance with previous studies (Alavi et al, 2001;Ladekarl, 2001;Mossin & Ladekarl, 2004;Christiansen et al, 2006;van der Salm et al, 2006) which found that canopy interception accounted for the major differences in percolation between deciduous and coniferous forests. As future afforestation projects mainly focus on broadleaved forest types it is also relevant to evaluate which deciduous species will yield the highest amount of percolation water and at the same time retain N.…”
Section: Water Balancesupporting
confidence: 93%
“…It was possible to simulate the water balance adequately at Mattrup and Vall based on calibration of simulated input of water to measured values of throughfall and subsequent calibration of simulated soil water content. Chloride flux balances are often used in studies of forest water balances to validate water balance simulations (Ladekarl, 2001;Mossin & Ladekarl, 2004;van der Salm et al, 2006). As chloride is assumed to be a conservative element in the environment the input flux should ideally be equal to the leaching flux, but the response of the leaching flux to chloride input events can be delayed for long periods due to changes in soil water storage and uncertainties of chloride concentration measurements (Wood, 1999;van der Salm et al, 2006).…”
Section: Water Balancementioning
confidence: 99%
“…For Ei the shares are 18% for beech and 46% for N. spruce, thus the interception loss in spruce is more than twice of that in beech. A high interception loss in spruce forests was also reported by Alavi et al (2001) and Mossin and Ladekarl (2003). Mossin and Ladekarl also concluded that a high interception loss would lead to low percolation.…”
Section: Simulations Of Water Balancesupporting
confidence: 57%
“…The K c value used for forest is relatively high. However, on the basis of investigations by Mossin and Ladekarl [2004] and van der Salm et al [2006] evaporation from the intercepted water is responsible for a relatively high potential evapotranspiration from conifer trees in this area.…”
Section: Methodsmentioning
confidence: 98%